High rate of hepatitis C virus and human immunodeficiency virus false‐positive results in serologic screening in sub‐Saharan Africa: adverse impact on the blood supply. Issue 1 (27th November 2019) - Candotti, Daniel; Sauvage, Virginie; Cappy, Pierre; Boullahi, Mohamed Abdallahi; Bizimana, Pascal; Mbensa, Guy Olivier; Oumar Coulibaly, Sekou; Rakoto Alson, Aimée Olivat; Soumana, Hadiza; Tagny‐Tayou, Claude; Murphy, Edward L.; Laperche, Syria; et al.
Abstract : BACKGROUND: False positivity in blood screening may cause unnecessary deferral of healthy donors and exacerbate blood shortages. An international multicenter study was conducted to estimate the frequency of HCV and HIV false seropositivity in seven African countries (Burundi, Cameroon, Democratic Republic of Congo, Madagascar, Mali, Mauritania, and Niger). STUDY DESIGN AND METHODS: Blood donations were tested for hepatitis C virus (HCV) and human immunodeficiency virus (HIV) with rapid detection tests (RDTs), third‐generation enzyme immunoassays (EIAs), or fourth‐generation EIAs. HCV (456/16, 613 [2.74%]) and HIV (249/16, 675 [1.49%]) reactive samples were then confirmed with antigen/antibody assays, immunoblots, and nucleic acid testing. Partial viral sequences were analyzed when possible. RESULTS: The HCV reactivity rate with RDTs was significantly lower than with EIAs (0.55% vs. 3.52%; p < 0.0001). The HIV reactivity rate with RDTs was lower than with third‐generation EIAs (1.02% vs. 2.38%; p < 0.0001) but similar to a fourth‐generation assay (1.09%). Only 16.0% (57/357) and 21.5% (38/177) of HCV and HIV initial reactive samples, respectively, were repeatedly reactive. HCV and HIV infections were confirmed in 13.2% and 13.7%, respectively, of repeated reactive donations. The predominant HCV genotype 2 and 4 strains in West and Central Africa showed high genetic variability. HIV‐1 subtype CRF02_AG was most prevalent. CONCLUSION: High rates (>80%) of unconfirmed anti‐HCV and anti‐HIV reactivity observed in several sub‐Saharan countries highlights the need for better testing and confirmatory strategies for donors screening in Africa. Without confirmatory testing, HCV and HIV prevalence in African blood donors has probably been overestimated.